Crimean–Congo hemorrhagic fever nosocomial infection in a immunosuppressed patient, Pakistan: Case report and virological investigation1. Issue 3 (21st November 2012) - Hasan, Zahra; Mahmood, Faisal; Jamil, Bushra; Atkinson, Barry; Mohammed, Murtaza; Samreen, Azra; Altaf, Lamia; Moatter, Tariq; Hewson, Roger
Abstract Crimean–Congo hemorrhagic fever (CCHF) is endemic in the Baluchistan province, Pakistan. Sporadic outbreaks of CCHF occur throughout the year especially in individuals in contact with infected livestock. Nosocomial transmission remains a risk due to difficulties in the diagnosis of CCHF and limited availability of facilities for the isolation of suspected patients. Rapid diagnosis of CCHF virus infection is required for early management of the disease and to prevent transmission. This study describes the case of a 43‐year‐old surgeon who contracted CCHF during a surgical procedure in Quetta, Baluchistan and who was transferred to a tertiary care facility at the Aga Khan University Hospital, Karachi within 1 week of contracting the infection. Diagnosis of CCHF was made using a rapid real‐time reverse transcription polymerase chain reaction (RT‐PCR) assay for CCHF viral RNA. The patient had chronic hepatitis B and hepatitis D infection for which he had previously received a liver transplant. He proceeded to develop classic hemorrhagic manifestations and succumbed to the infection 14 days post‐onset of disease. There was no further nosocomial transmission of the CCHF during the hospital treatment of the surgeon. Early diagnosis of CCHF enables rapid engagement of appropriate isolation, barrier nursing and infection control measures thus preventing nosocomial transmission of the virus. J. Med. Virol. 85:501–504, 2013. © 2012 Wiley Periodicals, Inc.